Colour-Based Extraction Methods for the Classification of Breast Milk (ASI) - Rogayah Rogayah; Waliya Rahmawanti; Nur Azizah (CCIT (Creative Communication and Innovative Technology) Journal, 2021)
The development of cellular devices makes accessing information in the form of text or images more easier. In line with the growing field of computer vision, various processes in image/image processing continue to increase. Image processing can be done by increasing image quality (image enhancement) and image recovery (image restoration). Feature extraction is divided into three types, namely feature form extraction, texture feature extraction, and color feature extraction. The application of color-based feature extraction methods has been widely used by researchers in the process of classification of various objects. This paper aims to review the technology that can be applied to image processing in a CBIR system with the object of breast milk so that it can measure the quality of breast milk based on its color.